Socialization of Introduction to Food Additives and Their Impact on Health for Students of Private High School Harapan 3 - Ritonga, Ahmad Hafizullah; Herlina, Herlina; Harefa, Karnirius; Harahap, Hasni Yaturramadhan; Sitorus, Rotua Sumihar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
The increase in processed food consumption has led to an increase in the use of food additives. However, public understanding of food additives and their health impacts remains minimal, especially among high school students. Private High School Harapan 3 is one such private school located in Deli Serdang Regency, North Sumatra, bordering the city of Medan, which has garnered attention due to the high number of students consuming food or snacks containing additives without knowing the negative effects of excessive consumption. This forms the basis for the need to conduct awareness activities at the school. Therefore, this community service activity aims to provide a better understanding to students as participants about food additives and their negative health effects. The implementation method of this activity consists of several stages. Firstly, the preparation of interesting and easily understandable counseling materials, covering the introduction of additives, their types, and their health impacts. Secondly, direct counseling conducted by lecturers from various disciplines interactively by providing relevant case examples. Thirdly, group discussions to deepen understanding and resolve participants' doubts. Fourthly, a question and answer session. The results of this activity show an improvement in participants' understanding, evident from their enthusiasm in asking questions because they realize the importance of choosing healthy foods and avoiding those with excessive additives. Group discussions help them understand information more deeply, while the question and answer session provides an opportunity to clarify doubts. Through this activity, we have successfully increased participants' understanding of food additives and their health impacts. Thus, participants are expected to apply this knowledge in their daily lives as smart and responsible consumers when choosing food.